2019
DOI: 10.1016/j.pursup.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Backshoring of production activities in European manufacturing

Abstract: This note presents empirical evidence on production backshoringthe movement of production activities from locations abroad back to the home country. Between 2010 and Mid-2012, only four percent of all firms moved production activities back to their home country. For every backshoring firm, there are more than three offshoring firms. Thus, from today's perspective it is unlikely that backshoring will be an important driver of a 'manufacturing renaissance' in Europe. The most frequent reason for backshoring is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 49 publications
(2 reference statements)
3
113
0
5
Order By: Relevance
“…Table VI presents a comparative summary of the results from this study with previous survey results from other geographical regions, i.e. from New Zealand (Canham and Hamilton, 2013), Europe (Dachs and Kinkel, 2013), and Germany (Kinkel and Zanker, 2013), that present comparable results to this study. These studies report on extent (in terms of the number of companies that offshore and backshore), type of production, and drivers.…”
Section: Jmtm 294supporting
confidence: 79%
See 1 more Smart Citation
“…Table VI presents a comparative summary of the results from this study with previous survey results from other geographical regions, i.e. from New Zealand (Canham and Hamilton, 2013), Europe (Dachs and Kinkel, 2013), and Germany (Kinkel and Zanker, 2013), that present comparable results to this study. These studies report on extent (in terms of the number of companies that offshore and backshore), type of production, and drivers.…”
Section: Jmtm 294supporting
confidence: 79%
“…In general, survey results give a concurrent picture indicating that backshoring of manufacturing increases with firm size, even though SMEs have become more active in recent studies. The most active firms can be found in high-tech industries such as motor vehicles and transport equipment (Dachs and Kinkel, 2013). The geographical regions most commonly involved in manufacturing relocation in the German studies are Eastern Europe (the 12 new EU member states), China and the rest of Asia, of which Eastern Europe appears to be the most attractive region for both offshoring and backshoring.…”
Section: Backshoring Vs Offshoringmentioning
confidence: 99%
“…3) Backhsoring for insourcing -transfer of production from foreign supplier (offshore outsourcing) to within firm's structures in its home country; 4) Outsourced backshoring -transfer of production from firm's foreign supplier to a supplier in its home market. Consequently in the forthcoming sections of the paper, based on Dachs and Zanker's (2015) proposition, backshoring is understood as a relocation of firm-owned value-adding activities from abroad to the home country of the firm. It is further recognised that such relocations are highly heterogenous in terms of production specificity, value and employment levels and predominantly, although not exclusively, do not involve the full repatriation or closure of entire company's offshore activities (Fratocchi et al 2014).…”
Section: The Scope Of Backshoringmentioning
confidence: 99%
“…The fragmented evidence sheds some light on key trends, including the scale, sectors, firm characteristics and motivation (e.g. Fisch & Zschoche 2012, Ellram et al 2013, Dachs & Zanker, 2015, Robinson & Hsieh 2016.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the CBI European survey in 2014 found that one-third of the surveyed firms had moved production back to their home market in the last three years (Wilkinson, Gregory and Arnold, 2015). Dachs and Kinkel (2013) also report a similar ratio of backshoring in offshoring firms, based on 3,300 companies from the European Manufacturing Survey. In a recent survey, 21 percent of US-based manufacturing firms said that they were moving back to the US (The Boston Consulting Group, 2013).…”
Section: Introductionmentioning
confidence: 86%